Zoom Fatigue during the COVID-19 Pandemic: Is it Real? - Lestari, Putri Winda; Fayasari, Adhila (Kesmas, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has caused drastic changes to social lives moreover the activities done outside, such as work and school. The policy of large-scale social restrictions (LSRR)/Pembatasan Sosial Berskala Besar (PSBB), which makes people stay at home, also plays an important role in changing the face-to-face activity online. As a solution to the major change, people use video conferencing to keep in touch and still feel like doing "offline" activities. The increasing use of video conferencing has raised concerns about the resulting fatigue, termed "Zoom fatigue." This study aimed to describe Zoom fatigue during the COVID-19 pandemic and the factors contributing to it. This study used a cross-sectional design with 376 participants. Data were gathered by completing a 45-item online questionnaire, which was analyzed using univariate, bivariate (Chi-square), and multivariate (binomial logistic regression) analyses. It was found that 68.6% of respondents experienced Zoom fatigue at a moderate to a high level. Respondents complained of se - veral symptoms related to activity, motivation, and physical weakness after using the video platform. In brief, Zoom fatigue is real, and the frequency of video platform use is related to the incidence of Zoom fatigue.